Characterization of the degradation performance of the sulfamethazine antibiotic by photo-Fenton process - Pérez Moya, Montserrat (2010)
The present study provides results describing the degradation performance of the Sulfamethazine (SMT) antibiotic via photo-Fenton treatment. Experiments were carried out using 1L solution samples of SMT (50mgL-1) under different conditions. HPLC results reveal that both Fenton and photo-Fenton reactions were able to completely remove SMT antibiotic from the studied samples in less than 2min treatment. Half-life times and kinetic parameters (assuming a pseudo-first-order kinetics at reaction initial stage, far from the equilibrium) for SMT degradation were determined and discussed. Hence, appropriate Fenton reagent loads are given to attain different targets proposed. TOC and HPLC data also revealed the presence of reaction intermediates; thus toxicity assays were performed regarding bacterial growth rate. The toxicity of an SMT solution was shown to increase during its degradation by means of photo-Fenton reactions.